In vitro antibacterial activity of hibiscus rosa sinensis leaf axtracts against some pathogens associated with urinary tract infections. - Cabayao, Coney B.
The in vitro antibacterial activity Hibiscus rosa sinensis leaf ( methanolic, dichloromethne, ethyl acetate , n-hexane, and aqueous ) extracts were studied against gram negative ( Escherichia coli and Pseudomonas aeruginosa ) and gram positive (Streptococcus faecalis ) bacteria. The methanolic extract was subjected to sequential liquid-liquid extraction using solvents of varying polarity and concentrations. Out of the 5 extracts, methanolic and dichloromethane extracts exhibited the highest antibacterial activity as measured using the zone of inhibition. This was followed by ethyl acetate and n-hexane extracts. At 200 mg/ml concentration, all extracts were considered active when tested with E. coli and S. faecalis, and were partially active against P. aeruginosa. The aqueous extract was inactive towards the three bacteria. the 200mg/ml concentrations showed no significant difference when comapred with the positive control, amoxicillin (12.51ug/ml). This shows that Hibiscus rosa sinensis exhibit a promising antibacterial activity., Phytochemical analysis of the active fraction - the methanolic extract, showed the presence of lakaloids, tannins, glycosides, saponins, steroids, flavonoids, terpenoids, and antraquinones. These bioactive components could be responsible for the antibacterial activity of Hibiscus rosa sinensis leaf extracts.